Parapharyngeal abscess in immunocompromised patients - Gani AN,; Abdullah A,; Hazim MYS,; Rozman Z, (Penerbit UKM, 2007)
Parapharyngeal abscess is a serious medical condition that may lead to life-threatening complications. Its incidence has dramatically decreased since the advent of antibiotics. We report two cases of parapharyngeal abscesses in immunocompromised patients. We believe that early diagnosis, broad-spectrum antibiotics, surgery and pus drainage can prevent serious complications